2014
DOI: 10.1519/jsc.0000000000000521
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographical Comparison of Plank Variations Performed With and Without Instability Devices

Abstract: Although there are multiple studies involving abdominal musculature activation and instability devices (e.g., Swiss balls), there is minimal research comparing them with a suspension device (e.g., TRX). The purpose of this investigation was to measure the electromyographical (EMG) activity of the rectus abdominis (RA), external oblique (EO), and erector spinae while performing planks with and without multiple instability devices. Twelve apparently healthy men (n = 6; age = 23.92 ± 3.64 years) and women (n = 6;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 13 publications
4
64
0
16
Order By: Relevance
“…11 Slings are ef-gating the effects of sling exercises with the inclusion of hip abduction are lacking. Previous studies reported that use of slings during exercises provide an unstable surface and therefore increase muscle activity compared with the general plank exercise, 15 and plank exercises combined with hip abduction are more effective than the general plank exercises. 10 Therefore, this study was conducted to investigate the effects of performing plank exercises with hip abduction with use of a sling on trunk muscle activity, to determine which plank exercise position would create the most effective trunk muscle activation, and to propose the steps to be applied to the exercise intervention according to the muscle activities.…”
Section: Introductionmentioning
confidence: 95%
“…11 Slings are ef-gating the effects of sling exercises with the inclusion of hip abduction are lacking. Previous studies reported that use of slings during exercises provide an unstable surface and therefore increase muscle activity compared with the general plank exercise, 15 and plank exercises combined with hip abduction are more effective than the general plank exercises. 10 Therefore, this study was conducted to investigate the effects of performing plank exercises with hip abduction with use of a sling on trunk muscle activity, to determine which plank exercise position would create the most effective trunk muscle activation, and to propose the steps to be applied to the exercise intervention according to the muscle activities.…”
Section: Introductionmentioning
confidence: 95%
“…Among them, we chose pectoralis major, quadriceps femoris, erector spinae for measuring trunk and low extremity activity (Byrne et al, 2014;Harris et al, 2017;Snarr and Esco, 2014 …”
Section: Study Proceduresmentioning
confidence: 99%
“…12,No. 3 increases activities of abdominal muscles among trunk muscles thereby strengthening trunk muscles without too much pressure on the spine (Snarr and Esco, 2014). The movements and activities of arms and legs affect the motion of the trunk.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…The results showed a higher level of activation for the Pectoralis Major compared to the Latissimus Dorsi during the pullover exercise. Additionally, Ab Wheel Rollout exercise can be mechanically compared to the static prone plank exercise in terms of trunk stabilization (flexors and extensors), 18,19 but the long lever-arm required during Ab Wheel training would conceivably alter muscle activation levels and perhaps the involvement of different trunk muscles.…”
Section: Data Analysesmentioning
confidence: 99%